Upaya Kasasi Penuntut Umum Atas Dasar Pengabaian Hal-Hal yang Memberatkan dan Pertimbangan Mahkamah Agung Memutus Perkara Pembakaran Lahan untuk Perkebunan - Marthin - (Sebelas Maret University, 2019)
This research aims to fnd conclusion of problems, frst, what is the reason of Cassation the public prosecutor on the basis of Aggravating Abandonment in the case of burning land to plantations has in accordance with article 253 Criminal Procedure Code in conjunction (KUHAP). Second, whether the Supreme Court’s consideration of granting the criminal sanctions and fnes have been in accordance with article 193 Article jo 256 paragraph (1) Criminal Procedure Code in conjunction (KUHAP). The results of the writing of the law explained that the frst reason, the submission of the appeal by the public prosecutor on the basis of a waiver the incriminating things in the case of burning land to plantations has in accordance with article 253 Criminal Procedure Code in conjunction (KUHAP) about the terms of the petition for cassation. as for the reason of application for appeal by the public prosecutor because Judex Factie had erred in applying the law, especially the law of criminal procedure that is less in considering things that weigh on the defendant (onvoldoende gemotiveert). Secondly, Consideration of the Supreme Court granted the criminal sanctions and fnes have been in accordance with article 256 Criminal Procedure Code in conjunction (KUHAP) exlain about the authority granting the petition of the Supreme Court of Cassation and revoke the requested verdict of Cassation, and Article 193 paragraph (1) Criminal Procedure Code in conjunction (KUHAP) explain when the defendant is proven to do the crime then the Court has the right to drop the criminal, therefore judges in meting out criminal in this case due to the consideration of Aggravating Abandonment on the defendant based on facts at trial.Keywords: Cassation, Aggravating Abandonment, burning land case